Comparison Study of BOD & COD of Leachate Quality (Case Study in Air Dingin Landfill and Jatibarang Landfill - Aidah Maqbulah Al-Hadi; Diah Ayu Lestari; Julio Putra David (Journal of Environmental Engineering and Waste Management, 2019)
Abstract: Leachate is one of the products that produced by a landfill. Leachate is extremely potential to pollute the environment, such as soil, groundwater and surface water. Air Dingin and Jatibarang landfill have a treatment to treat the leachate produced by the landfill before it is discharged to the environment because it has to be in accordance with Regulation of Ministry of Environment and Forestry of Republic of Indonesia Number P.59/Menlhk/Setjen/Kum.1/7/2016 concern Leachate Standard Quality for Businesses and/or Activities of Landfill. The leachate management in Air Dingin Landfill is controlled landfill, while in Jatibarang landfill, the the leachate management is coagulation-flocculation system.  COD and BOD contained in Air Dingin Landfill leachate is lower than Jatibarang Landfill. In order to make leachate more environmental  friendly, some innovative methods for leachate management have been developed, such as biofilter, wetlands, coagulation-fluctuation, and electrocoagulation.